2005
DOI: 10.1038/sj.emboj.7600694
|View full text |Cite
|
Sign up to set email alerts
|

SCAN1 mutant Tdp1 accumulates the enzyme–DNA intermediate and causes camptothecin hypersensitivity

Abstract: Tyrosyl-DNA phosphodiesterase (Tdp1) catalyzes the hydrolysis of the tyrosyl-3 0 phosphate linkage found in topoisomerase I-DNA covalent complexes. The inherited disorder, spinocerebellar ataxia with axonal neuropathy (SCAN1), is caused by a H493R mutation in Tdp1. Contrary to earlier proposals that this disease results from a loss-of-function mutation, we show here that this mutation reduces enzyme activity B25-fold and importantly causes the accumulation of the Tdp1-DNA covalent reaction intermediate. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
209
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(231 citation statements)
references
References 46 publications
9
209
2
3
Order By: Relevance
“…3C) [40]. The second S N 2 reaction step in the Tdp1 catalytic mechanism is supported by in vitro biochemical studies with the SCAN1 H493R mutant, which leads to an accumulation of Tdp1-DNA covalent intermediate [28]. Overall, the final product released after Tdp1 catalysis is a DNA molecule with a 3′-phosphate end (Fig.…”
Section: Biological Functions and Catalytic Mechanismmentioning
confidence: 68%
See 2 more Smart Citations
“…3C) [40]. The second S N 2 reaction step in the Tdp1 catalytic mechanism is supported by in vitro biochemical studies with the SCAN1 H493R mutant, which leads to an accumulation of Tdp1-DNA covalent intermediate [28]. Overall, the final product released after Tdp1 catalysis is a DNA molecule with a 3′-phosphate end (Fig.…”
Section: Biological Functions and Catalytic Mechanismmentioning
confidence: 68%
“…Specifically, homozygous mutant SCAN1 cells have been shown to accumulate more total DNA strand breaks than normal lymphoblastoid cells after treatment with CPT [24,72]. SCAN1 cells have also demonstrated enhanced sensitivity to the killing effects of CPT [28,72]. Furthermore, complementary studies have shown that overexpression of wild-type Tdp1 protects cells against CPT-induced cell death [26,73], whereas the inactive mutant Tdp1 H263A does not [26].…”
Section: Rationale For Targeting Tdp1 For Cancer Therapymentioning
confidence: 84%
See 1 more Smart Citation
“…CPT-induced cell death was also observed in yeast and human tdp1 mutants. The human Tdp1 gene in SCAN1 cells is hypersensitive to CPT and induces cell death in treated cells (El-Khamisy et al, 2005;Interthal et al, 2005). Yeast tdp1 mutants, when coupled with mutation of the other DNA repair genes, show a significant effect on the survival of CPT-treated cells Liu et al, 2002Liu et al, , 2004Vance and Wilson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As in yeast, the human Tdp1 protein plays a role in the repair of topoisomerase I-DNA complex lesions in SCAN1 cells (El-Khamisy et al, 2005;Miao et al, 2006). SCAN1 cells are hypersensitive to CPT (Interthal et al, 2005;Miao et al, 2006) and accumulate single-strand break and double-strand break DNAs by CPT (El-Khamisy et al, 2005).…”
mentioning
confidence: 99%